Experimental studies on the effect of chromium plating on the mechanical properties of SAE 4140 steel. (2023) - Akhtar, M.N.; Lohchab, Amal; Singh, D.; Kumar, R.R.; Gaur, Piyush; Yadav, B.K.
Abstract: Chrome plating is a technique of electroplating a thin layer of chromium onto a metal object. The effects of chromium plating on the mechanical properties of SAE 4140 steel using tensile, compression, flexural, Vickers hardness, corrosion and wear tests have been studied and determined. In tensile tests, the yield stress of chromium-coated coupons (846.02 MPa) is less than that of virgin coupons (958.08 MPa). The same pattern was observed in the compression tests when the chromium-coated coupon's compression load (71.26 kN) was less than that of the virgin coupons (75.08 kN). However, the flexural test of the chromium-coated coupons showed greater flexural strength than those of the virgin coupons. The Vickers hardness number (415HV.050) is less for virgin coupons as compared to coated samples (1026HV.050), (1286HV.050), and (1371HV.050). As we increase the coating thickness percentage from 0.0508 mm to 0.508 mm, the Vickers hardness number increases, whereas the chromium-coated coupon's corrosion resistance and wear resistance were found to be more significant.